IMPROVING THE QUALITY AND RELEVANCE OF RESEARCH OUTPUTS THROUGHOUT PUBLISHING IN SCHOLARLY JOURNALS - Al-Eknah, Marzook M. (European Scientific Journal, ESJ, 2013)
This article is intended to stimulate the culture of accomplishing top researches and publish their results in good repute journals. Scholarly publication needs scholarly research and scholarly research needs scholarly researchers. It is sometimes difficult to distinguish between the non-scholarly (peripheral) and scholarly journals. The main difference is the depth of research and the intrinsic value of results. Bibliometricians introduced indicators, depending mainly on citations, to evaluate and rank the journals. Scholarly writing depends on the publication format, which in turn relies on the research discipline of humanities, social sciences, basic and applied sciences, engineering, technology, computing sciences, and information technology. Although lots of publications are faced with lots of rejections, there is still a chance that manuscript rejected by one journal may be accepted by another journal, in addition, a journal may not accept a manuscript as it has huge backlog while another scholarly journal may be hungry to receive a manuscript. However, for scholarly writing the authors must follow the journal guidelines to prepare the manuscript and they should not send the manuscript to the editor until having it reviewed with a fresh eye. The publication speed usually takes from weeks to months. However, one can predict the turnaround speed of publication from the colleagues or look at sample of articles published where written on the first page the date of receipt and publication. This article is also intended to build up a researching character able to react with the criticism imposed by the editor or reviewers.